Management of Stomatitis Apthous Recurrent in Patients with Multiple Systemic Diseases - Case Report - Surachmin, Audiawati; Fathia Sabila; Ahmad Ronal; Nurfianti (YARSI Dental Journal, 2024)
Introduction: A 63 year old patient with multiple systemic diseases came in complaining that there were many ulcer in his oral cavity. Providing the best treatment for ulcers in the patient's oral cavity. Case Report: A 63 year old male patient came to RSGM YARSI on March 20 2019 with complaints of mouth ulcers on the left side of his tongue for the previous 3 days. The patient had a history of heart disease and hypertension for 8 years and had undergone heart surgery. History of stroke occurred 3 months ago. During the visit, the patient also informed that he was taking medication related to his illness.  Discussion: The patient received garg therapy. Chlorhexidine gluconate 0.2% and ungt. Triamcinolone acetonide 0.1% 5gr to reduce pain and eliminate bacteria and fungi. During the 1 week follow-up, there were still lesions but they were no longer painful. In the second week, the lesions had disappeared and healed. Conclusion: In this case, we found an ulcerated lesion on the patient's left ventral tongue. The cause of the lesion is unknown but is suspected to be predisposing factors such as drugs, systemic disease and poor oral hygiene conditions.